Taxonomic revision of species of Haematoloechus Looss, 1899 (Digenea: Plagiorchioidea), with molecular phylogenetic analysis and the description of three new species from Mexico - León-Règagnon, Virginia; Topan, Janet (Zootaxa, 2018)
Lung flukes of the genus Haematoloechus Looss, 1899 are common parasites of anurans worldwide, but the taxonomy of the group has been confusing. In this taxonomic revision, 89 species of Haematoloechus (= Pneumonoeces Looss, 1902, Ostioloides Odening, 1960, Ostiolum Pratt, 1903, Skrjabinoeces Sudarikov, 1950, Neohaematoloechus Odening, 1960, Metahaematoloechus Yamaguti, 1971) are listed. Of these, 70 are considered valid, three are species inquirendae (H. legrandi Mañé–Garzón & Gil, 1959, H. latoricensis Kozák, 1968 & H. vitelloconfluentum (Rai, 1962) Saeed, Al–Barwari & Al-Harmni, 2007), one is a nomen nudum H. sudarikovi Belouss, 1962, 14 are junior synonyms and one belongs to Ostioloides. This publication also describes three new species, H. occidentalis n. sp., H. veracruzanus n. sp. and H. mexicanus n. sp., parasitizing species of Rana Linnaeus in Mexico and redescribes Haematoloechus caballeroi (Skrjabin & Antipin, 1962) Yamaguti, 1971. The phylogenetic hypotheses based on sequences of mitochondrial and ribosomal DNA of Haematoloechus spp. show that genera proposed on the basis of morphological characters are not supported. The host records for species of Haematoloechus, together with the phylogenetic hypothesis of the genus, suggest that this host-parasite association predates the ranid diversification in the Cretaceous.